Innovation in Authentic Assessment in Islamic Religious Education Learning in the Digital Era - Ramli, Rosmiati; Na’iem, Muharrir; Ustar, Nur Aisyah; Muminayah, Muminayah; Assam, Abdul (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The development of digital technology has brought significant changes to various aspects of education, including learning assessment systems. Islamic Religious Education (IRE), as a subject aimed at shaping students who are faithful, knowledgeable, and possess noble character, requires a comprehensive and contextual assessment approach. Authentic assessment emerges as an alternative evaluation method that holistically measures students’ cognitive, affective, and psychomotor domains through tasks that reflect real-life situations. This paper aims to examine the concept of authentic assessment, its innovative forms in Islamic Religious Education learning in the digital era, as well as the challenges and opportunities of its implementation. This study employs a qualitative approach through a literature review of recent scholarly sources, educational regulations, and both classical and contemporary literature in Islamic education. The findings indicate that the integration of digital technology into authentic assessment in Islamic Religious Education can enhance the objectivity, efficiency, and relevance of assessment, while also supporting the internalization of Islamic values in students’ daily lives. Therefore, strengthening teachers’ competencies and developing digital-based assessment instruments are urgent needs in the advancement of Islamic Religious Education learning.